A Hydrogen-Vanadium Reversible Fuel Cell Crossover Study. Issue 14 (1st January 2017) - Dowd, Regis P.; Verma, Ankit; Li, Yuanchao; Powers, Devon; Wycisk, Ryszard; Pintauro, Peter N.; Van Nguyen, Trung
Abstract : Vanadium crossover through the ion exchange membrane in vanadium-based redox flow battery systems results in self discharge and variations in electrolyte concentration. VO + 2 and VO + 2 crossover rate, or permeability, through various Nafion membranes was measured directly with a hydrogen-vanadium reversible fuel cell. Measuring crossover of electrolyte species directly with a fuel cell, as compared to an idealized dual-chamber system, allows for determining permeability under actual fuel cell testing conditions. This new in-situ technique for measuring VO + 2 and VO + 2 crossover with a fuel cell is shown to be reliable and easy to use. The crossover measurement method shows increased crossover rates with thinner ion exchange membranes. Electrospun blended nanofiber membranes were also fabricated and tested in the hydrogen-vanadium reversible fuel cell leading to lower crossover rates and high fuel cell performance, as compared to commercial Nafion films.